Validation of the fast dose calculator for Shanghai Proton and Heavy Ion Center. (20th September 2018) - Wang, Qianxia; Schlegel, Nicki; Moyers, Michael; Lin, James; Hong, Liu; Chen, Hongliang; Johnson, Avery; Li, Jie; Shen, Zhuangming; Xu, Meiling; Taddei, Phillip J; Yepes, Pablo
Abstract: The fast dose calculator (FDC), a track-repeating algorithm that was initially developed for proton therapy, has been expanded to include carbon. The purpose of this study was to validate FDC as a dose engine for treatment planning of scanning proton and carbon beams at the Shanghai Proton and Heavy Ion Center (SPHIC). For a complete set of clinical reference beams, the absorbed dose calculated with FDC was compared with that measured. A gamma-index analysis found over 94.6% and 100.0% of the measured points for protons had a gamma-index value smaller than unity for the 1%/1 mm and 1.5%/1.5 mm dose/distance agreement criteria, respectively. For carbon, the passing rates were above 80.6% and 92% with and without ripple filter if the criteria was set to 1%/1 mm. The values increased to 90.0%and 96.0% with the criteria 1.5%/1.5 mm. In conclusion, we found that FDC can serve as an accurate dose calculation engine for the SPHIC.